Comparative Analysis of Cervical Cell Classification Using Machine Learning Algorithms - Wan Azani Mustafa; Khalis Khiruddin; Khairur Rijal Jamaludin; Firdaus Yuslan Khusairi; Shahrina Ismail (2026)
Indexed by SCOPUS